Fisheries Sector and Women in Bangladesh - Ali, Mir Mohammad (Sher-e-Bangla Agricultural University, 2023)
Women’s empowerment in promoting the fisheries sector is not encouraged in Bangladesh. The study explored how empowering women in the fisheries sector can contribute to achieving more equitable, inclusive, and sustainable fisheries and food systems. The research adopts a qualitative approach, combining in-depth interviews, focus group discussions, and participatory observation methods. The findings highlighted the critical role of women’s empowerment in challenging. Women’s empowerment initiatives, such as access to education, skills training, and leadership opportunities, enable women to challenge traditional gender roles and stereotypes, enhance their self-esteem and agency, and improve their socioeconomic status. These include supportive policies and legal frameworks, access to credit and financial services, inclusive and genderresponsive institutions, and the recognition of women’s contributions and rights. Social and cultural norms, discriminatory practices, and lack of awareness about the benefits of women’s empowerment are identified as major barriers that need to be addressed for sustainable gender transformation. The study emphasizes the importance of multistakeholder collaborations and partnerships to foster women’s empowerment and transformative change in agri-food systems, specifically within fisheries. It highlights the need for inclusive and gender-responsive policies, programs, and interventions that address the specific needs and challenges faced by women in the fisheries sector. Additionally, capacity-building programs, awareness campaigns, and targeted support for women’s entrepreneurship and market access are recommended to enhance women’s participation and leadership in the sector.